The Correlation of Therapeutic Communication in Nursing and Patient Satisfaction during caring in Hospital - Priyantini, Diah (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
Introduction: Therapeutic communication is important in patient care at the hospital in every patient activity and healing. This communication includes verbal and non-verbal communication. Patient satisfaction can be fulfilled if the communication provided is as expected, if not, patient dissatisfaction will arise. This study aimed to determine the correlation between therapeutic communication performed by nurses and patient satisfaction while in hospitalMethods: A cross sectional study in in the hospital with 36 patients. Total 33 respondents were recruited using consecutive sampling. Therapeutic communication and patient satisfaction measured using questionnaire. The collected data were analyzed using SPSS version 21 with the Spearman Rho Test.Results: The results showed that most of the nurses' therapeutic communication was good as many as 21 respondents (63.6%). Meanwhile, for patient satisfaction, 17 respondents (51.4%) said they were satisfied. From the results of the Spearman Rho test, it was found correlation between therapeutic communication performed by nurses and patient satisfaction while in hospital with p = 0.011 (p<0.05) and coefficient value was 0.438.Conclusion: Good therapeutic communication will help accelerate patient recovery and help patients to make decisions in nursing action procedures. The better the communication that is applied, the more satisfied the patient is in accepting and in accordance with his expectations.